SENSUAL ADVERTISING TVC “AXE UNIVERSITY” SEBAGAI REPRESENTASI KAPITALISME MEDIA DAN HYPERREALITAS PEREMPUAN INDONESIA - Ardhariksa Zukhruf Kurniullah (Universitas Bunda Mulia, 2015)
Sensual Advertising is advertising using sex appeal. Ads with female existence can not be separated, because women have the power to help selling the product being advertised. Researchers chose version TVC ad AXE University in 2014 as an advertising being analyzed as this ads shows the presence of symptoms and the exploitation of the female body as a representation of capitalism media. This research aims to analyze the presence of women in the AXE deodorant ad became a major commodity, knowing the media representations of capitalism and female hyperrealitas Indonesia in the ad TVC